Energy Efficiency of Microprocessor - Unwala, Husain; Shetye, Sairaj; Yadav, Abhishek; Shaikh, Shakila; Pappu, Shiburaj (International Journal of Computer Sciences and Engineering, 2019)
In the microprocessor industry we see that energy efficiency is one-off the main issues that we are faced with.The motivation for our paper is the increased applications which use embedded systems for communication and multimedia. In our paper you will see the changes in techniques that have made a considerable amount of development to make sure that the efficiency of the microprocessor consumes will be less but also not compromise with the performance (clock speed) that it provides to the users. Internet connectivity has caused the devices to be in use all day long because of this the rate at which the microprocessor runs uses great amount of energy because of which energy efficiency has to be good. Ever since caches were introduced they present the most attractive ways for power reduction. To implement coherent caches using MESI protocol we use snoop filtering mechanism.